Research on the Innovation Path of Business Models Based on the Market Orientation - Yongmei Ma; Huafei Wei; Chuanshuang Hu; Chenglin Jin (Complexity)
Current research considers business model innovation as a series of responses to technological change and market environment change. However, in practice, it is often business model innovation that leads to market innovation and subversion and then promotes a new round of iterative product renewal. This is because business model innovation is a value creation activity based on market demand, rather than a technology-oriented innovation behavior. Moreover, since the degree of demand manifestation varies, the degree of its influence on value creation and thus the driving mechanism for business model innovation vary significantly, and the duality of market-oriented theory is introduced to explore how firms go about achieving business model innovation based on different demand characteristics and how the results of firms’ integration of market information work. Through regression analysis of 230 sample enterprises, the results show that both responsiveness and proactive market orientation have a significant positive impact on business model innovation. In contrast, market information integration has a positive regulatory effect on the two groups of relationships.